A study on virtual internship in skills development and its relation towards students learning experience / Nor Allya Daniah Zuri and Siti Aishah Mohd Safieei - Zuri, Nor Allya Daniah; Mohd Safieei, Siti Aishah (2022)
This study was conducted to examine the student perception on virtual internship in skills development and its relation towards students' learning experience among UiTM’s Students in Campus Seremban. The skill developments observed in this are measured in terms of thinking skill, soft skill and technical skill. In this study, the research objective is to identify the level of student learning experiences in relation to virtual internship in skill developments. By utilizing purposive sampling and quantitative approach, a total of 381 respondents were given a set of questionnaires via online and need to be answered. However, only 110 people responded to this study. Basically, the respondents are the students from UiTM Seremban 3 with particular evaluation for Faculty of Admin Science and Policy Studies. By using IBM SPSS Statistics 20, all the feedback and response from the respondents will be analyzed in order to examine the relationship between these three skill developments, which are measured in terms of thinking skill, soft skill and technical skill with student learning experience. All of the skills mentioned above were found to have a positive significant relationship with the students' learning experiences among UiTM Students in Campus Seremban. Based on the research findings, the most influential skill development measured is technical skill.